2006
DOI: 10.1038/sj.onc.1209801
|View full text |Cite
|
Sign up to set email alerts
|

The 26S proteasome system degrades the ERM transcription factor and regulates its transcription-enhancing activity

Abstract: ERM is a member of the ETS transcription factor family. High levels of the corresponding mRNA are detected in a variety of human breast cancer cell lines, as well as in aggressive human breast tumors. As ERM protein is almost undetectable in these cells, high degradation of this transcription factor has been postulated. Here we have investigated whether ERM degradation might depend on the proteasome pathway. We show that endogenous and ectopically expressed ERM protein is short-lived protein and undergoes prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 40 publications
(43 reference statements)
1
17
0
Order By: Relevance
“…A major ERM species was observed at approximately 85 kDa in the Ni 2 þ -bound protein fraction as a result of Ub overproduction ( Figure 4a). As described earlier, it corresponds to a monoubiquitylated form of ERM (Baert et al, 2007). Higher molecular mass species, characteristic of polyubiquitylation (Baert et al, 2007), were also observed (Figure 4a, compare lanes 1 and 2).…”
Section: Etsmentioning
confidence: 63%
See 4 more Smart Citations
“…A major ERM species was observed at approximately 85 kDa in the Ni 2 þ -bound protein fraction as a result of Ub overproduction ( Figure 4a). As described earlier, it corresponds to a monoubiquitylated form of ERM (Baert et al, 2007). Higher molecular mass species, characteristic of polyubiquitylation (Baert et al, 2007), were also observed (Figure 4a, compare lanes 1 and 2).…”
Section: Etsmentioning
confidence: 63%
“…As described earlier, it corresponds to a monoubiquitylated form of ERM (Baert et al, 2007). Higher molecular mass species, characteristic of polyubiquitylation (Baert et al, 2007), were also observed (Figure 4a, compare lanes 1 and 2). In the presence of COP1, a slight increase in monoubiquitylation of ERM was observed, but polyubiquitylation was not enhanced (compare lanes 2 and 3).…”
Section: Etsmentioning
confidence: 63%
See 3 more Smart Citations